A SYSTEMATIC REVIEW: THE ASSOCIATION BETWEEN URINE LEUKOCYTES AND THE TYPES OF URINARY TRACT INFECTION - Sunjaya, Joshua; Bororing, Sheella Rima; Iryaningrum, Maria Riastuti (Indonesian Journal of Urology, 2022)
Objective: This study aimed to determine the functional role of the urine leukocyte count on type of UTI. Material & Methods: This is a systematic review study with searches for articles from 2010-2020 through the PubMed, ProQuest, and EBSCO databases. The exclusion criteria in this study are patients using catheters (CAUTI), UTI patients in the Intensive Care Unit (ICU), and pediatric or infant patients. There were 1158 studies found and 3 studies synthesized. Results: There are 1130 patients studied. Age range from 18 to 89.1 years. Three studies showed that there was an association between the number of urinary leukocytes and the type of UTI (Tommaso Cai et al., p < 0.0001; and Alexander R. Levine et al., p < 0.001) and one study had no relationship. Conclusion: There is a relationship between the number of urinary leukocytes with the type of UTI. An increase in the number of urinary leukocytes above the normal limit is the sign of body’s immune response to eliminate uropathogens. The innate immune characteristic factors and the body’s immune response have an important role in causing symptoms in UTI patients.